Surgical Management of Abnormally Invasive Placenta: A Retrospective Cohort Study Demonstrating the Benefits of a Standardized Operative Approach. Issue 4 (December 2016) - Brennan, D.J.; Schulze, B.; Chetty, N.; Crandon, A.; Petersen, S.G.; Gardener, G.; Perrin, L.
Abstract : ( Acta Obstet Gynecol Scand. 2015;94:1380–1386) Research has established that one of the major causes of maternal morbidity and mortality is an abnormally invasive placenta (AIP). AIP occurs when all parts or particular parts of the placenta do not separate from the uterine wall following delivery; this includes placenta accreta, increta and percreta. Complications of surgery to treat this problem include urologic and bowel injury, sepsis, fistula formation, and complications associated with massive blood loss and transfusion. Hence the objective of this study was to assess the role of a gynecologic oncologist's (GO) involvement in AIP cases with an emphasis on the surgical approach used and how this might affect maternal and neonatal morbidity.